2010
DOI: 10.1088/0004-637x/720/2/1721
|View full text |Cite
|
Sign up to set email alerts
|

A Solar Spectroscopic Absolute Abundance of Argon From Resik

Abstract: Observations of He-like and H-like Ar (Ar xvii and Ar xviii) lines at 3.949 Å and 3.733 Å, respectively, with the RESIK X-ray spectrometer on the CORONAS-F spacecraft, together with temperatures and emission measures from the two channels of GOES, have been analyzed to obtain the abundance of Ar in flare plasmas in the solar corona. The line fluxes per unit emission measure show a temperature dependence like that predicted from theory and lead to spectroscopically determined values for the absolute Ar abundanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 29 publications
7
30
1
Order By: Relevance
“…Sterling et al (1993) found that the calcium abundance in 25 events was on average about a factor of two greater than photospheric, indicating a coronal flare abundance. Sylwester et al (2010Sylwester et al ( , 2015 found argon abundances that are nearly the same as the Lodders (2008) argon abundance that we used in Doschek et al (2015). A photospheric argon abundance is expected if the low-FIP elements are enhanced in the corona.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Sterling et al (1993) found that the calcium abundance in 25 events was on average about a factor of two greater than photospheric, indicating a coronal flare abundance. Sylwester et al (2010Sylwester et al ( , 2015 found argon abundances that are nearly the same as the Lodders (2008) argon abundance that we used in Doschek et al (2015). A photospheric argon abundance is expected if the low-FIP elements are enhanced in the corona.…”
Section: Introductionsupporting
confidence: 61%
“…We used the same abundance sources as given in Doschek et al (2015): the calcium abundance is from Caffau et al (2011), and the argon abundance is from Lodders (2008). As mentioned, the Lodders (2008) argon abundance is nearly the same as found in flares by Sylwester et al (2010Sylwester et al ( , 2015. The photospheric line ratio is about unity.…”
Section: Eis Argon Spectramentioning
confidence: 99%
“…Here, for consistency with calculations of satellites of lower ionization stages, apart from a few exceptions we used the Cowan Hartree-Fock atomic code (Cowan 1981) to calculate the necessary data. This code was run previously in studies we made of X-ray dielectronic satellites of Li-like K and Cl seen with the RESIK instrument (Sylwester et al 2010b(Sylwester et al , 2011. The code 1 , outlined in Cowan (1981) (3) and (4) with g 1 = 2 for Ca XVII satellites (excitation from the ground level 1s 2 2s 2 S 1/2 of Ca +17 with statistical weight 2), 1 for Ca XVI (excitation from 1s 2 2s 2 1 S 0 of Ca +16 ), and 2 for Ca XV (excitation from 1s 2 2s 2 2p 2 P 1/2 of Ca +15 ).…”
Section: Ca XVIII -Ca Xv Dielectronic Satellitesmentioning
confidence: 99%
“…Figure 2 shows RESIK channel 1 spectra extracted from the new data set and summed over narrow regions of temperature T GOES , taken to be that estimated from the flux ratio of the two X-ray channels of the Geostationary Operational Environmental Satellites (GOES). Our previous work has indicated that T GOES is an accurate representation of temperature for the K XVIII lines as well as Ar XVII lines seen in channel 2 (Sylwester et al 2010a where N e = electron density and V = emitting volume) for each RESIK spectrum were estimated from the ratio of the observed spectral flux to the theoretical spectral flux from the CHIANTI code at the temperature T GOES . The vertical scale in Figure 2 is flux (photon cm −2 s −1 keV −1 ) normalized to a volume emission measure of 10 48 cm −3 .…”
Section: Observationsmentioning
confidence: 99%